Phenomenon of Smoking Behavior Among Adolescents Aged 10 to 18 Years in Parongpong District - Inkiriwang, Daniel Hasian; Triwahyuni, Palupi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Smoking habits among adolescents aged 10–18 have reached alarming levels in Indonesia. This study aims to further understand how adolescents develop an addiction and a compulsion to smoke. This study used a qualitative design with a phenomenological approach. Data were analyzed using the phenomenological interpretation method (IPA). The results showed that the primary source of cigarettes predominantly came from peers, followed by family, and a small portion came from personal initiative. Adolescents have basic knowledge about the dangers of smoking, but their knowledge is still limited. Attitudes toward anti-smoking movements tend to be neutral and are not considered important. Smoking behavior in adolescents is largely influenced by peer pressure, curiosity, the search for identity, and the desire for group acceptance. The phenomenon of smoking among adolescents in Parongpong District is influenced not only by health knowledge but also by social, symbolic, family, and adolescent psychosocial development factors. Smoking behavior is more influenced by the social meaning of cigarettes as a symbol of maturity and the process of identity search than by rational knowledge about health risks. Thus, this phenomenon is not only a health behavior, but also a complex social phenomenon.